Curves of Brocard points in triangle pencils in isotropic plane - Jurkin, Ema (Array, 2019)
In this paper we consider a triangle pencil in an isotropic plane consisting of the triangles that have the same circumscribed circle. We study the locus of their Brocard points, two curves of order 4.